Juridical Analysis of Procedures and Stages of Determining Criminal Suspects Against Perpetrators of Traffic Accidents Due to Negligence (Research Study at the Barelang Police Traffic Unit, Batam) - Anggara, Risky; Fadlan, Fadlan; Jihad, Kaspol; Prasetyasari, Christiani (CV. Rayyan Dwi Bharata, 2023)
The procedure and stages for determining a suspect in a traffic accident crime due to negligence are carried out in stages, receiving a report or complaint from someone about a criminal act, seeking information and evidence, in Article 311 of Law Number 22 of 2009. The sound of Article 311 is explained that paragraph (1) Every person who deliberately drives a motorized vehicle in a manner or condition that is dangerous to life or property shall be punished with a maximum imprisonment of 1 (one) year or a maximum fine of IDR 3,000,000.00 (three million rupiah). The problem in this research is what the law is, its implementation and what factors become obstacles and obstacles in the procedures and stages of determining suspects for perpetrators of criminal traffic accidents due to negligence. This research uses a descriptive analysis method using a normative approach (legal research) and is supported by empirical research. This was carried out to obtain primary data obtained through interviews through field research (research). The results of this research explain that Article 1 number 24 of Law Number 22 of 2009 concerning Road Traffic and Transportation states that a traffic accident is an unexpected and unintentional event on the road involving a vehicle with or without other road users which results in human casualties and/or property loss, minor traffic accidents which are accidents that result in damage to vehicles and/or goods, accidents that result in minor injuries and damage to vehicles and/or goods, serious traffic accidents. It is hoped that this will be done by providing education to the public. regarding traffic and safety when driving, little by little it will create a sense of caution among the public when driving. This aims at education which is carried out by carrying out activities such as seminars held in schools and factories.